Synthesis method of polybenzimidazole ion exchange membrane containing quaternization side chain
By introducing quaternized side chains into the polybenzimidazole ion exchange membrane to form a crosslinking network structure, the shortcomings of the perfluorosulfonic acid membrane in terms of ion selectivity are solved, the ion exchange capacity and conductivity of the membrane are significantly improved, and the mechanical properties and durability are enhanced.
Patent Information
- Application Number
- CN202510008969.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
In existing flow batteries, the commonly used perfluorosulfonic acid films have insufficient ion selectivity, resulting in asymmetric migration of active substances and causing capacity attenuation and efficiency of energy storage systems.
The synthesis method of a polybenzimidazole ion exchange membrane containing quaternized side chains is adopted. By blending polybenzimidazole with polyethylene benzyl chloride and introducing quaternary ammonium salt functionalized side chains, a crosslinking network structure is formed to improve the ion exchange capacity and conductivity of the membrane.
The ion exchange capacity and conductivity of the membrane are significantly improved, the transmission channels of anions are optimized, the ion migration resistance is reduced, the mechanical properties and durability of the membrane are enhanced, the service life is extended, and the frequency of maintenance and replacement is reduced.
Smart Images

Figure CN119798745A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage, and in particular relates to a method for synthesizing a polybenzimidazole ion exchange membrane containing a quaternized side chain. Background Art
[0002] As the proportion of renewable energy systems such as wind and solar energy in the power grid system gradually increases, the application of energy storage technology can ensure the stable operation of the power grid system. Redox flow batteries, as one of the electrochemical energy storage solutions, can adjust the intermittent nature of renewable energy. At the same time, this solution has significant advantages over lithium batteries in terms of maintainability, safety and adjustability, and is regarded as the most suitable electrochemical energy storage technology for long-term energy storage. At present, the mainstream flow battery system is the all-vanadium flow battery, which stores and releases energy through four different oxidation states of vanadium. The negative electrode and the positive electrode contain sulfuric acid aqueous solutions of V2+ / V3+ and VO2+ / VO2+, respectively, and the concentration of vanadium is 1.5-2mol / L. However, the ion exchange membrane provides physical isolation for the positive and negative electrolytes to prevent the cross-migration of vanadium ions, while allowing the passage of hydrated protons. Therefore, the ion exchange membrane needs to have a high proton conductivity while having good barrier properties. In addition, due to the requirements of the stack structure, the ion exchange membrane also needs to have a high mechanical strength.
[0003] At present, the common membrane materials in flow batteries are perfluorosulfonic acid, sulfonated polyetheretherketone and sulfonated polyimide. Among them, perfluorosulfonic acid membranes are favored by the market due to their antioxidant properties, high proton conductivity and high strength, and have been successfully applied in projects. The proton conduction mechanism of perfluorosulfonic acid membranes mainly depends on the hydration and protonation of sulfonic acid groups to form sulfonic acid hydrogen ions, and realize the rapid jumping and transfer of protons through the hydrogen bond network between water molecules. This process is affected by the microstructure, temperature, humidity and chemical stability of the membrane, so that the membrane exhibits efficient proton conduction performance in electrochemical devices. However, the ion selectivity of perfluorosulfonic acid membranes has always been criticized. During the application process, asymmetric migration of active substances at the two poles will occur, resulting in an imbalance of active substances, causing capacity decay and efficiency reduction of the energy storage system.
[0004] Polybenzimidazole is a type of polymer with benzimidazole units in the main chain, and its materials have excellent thermomechanical properties and chemical stability. At present, polybenzimidazole ion exchange membranes have been widely used in electrochemical fields, such as high-temperature fuel cells, electrolyzers, and flow batteries, because polybenzimidazole can combine with acids and bases to produce ion conductivity. In the field of flow batteries, common all-vanadium flow batteries and vanadium-iron flow batteries use high-concentration sulfuric acid, hydrochloric acid, etc. as supporting electrolytes. This concentration can achieve complete protonation of functional groups on polybenzimidazole ion membranes to form positively charged cationic polymers. In addition, due to its Donnan exclusion and spatial effect, the rejection rate of vanadium ions in polybenzimidazole ion exchange membranes is much better than that of perfluorosulfonic acid membranes, which can effectively alleviate the phenomenon of vanadium ion penetration and capacity attenuation. However, the proton conductivity of polybenzimidazole ion exchange membranes is much lower than that of perfluorosulfonic acid membranes. Therefore, in order to further improve the proton conductivity of polybenzimidazole ion exchange membrane, a method for synthesizing polybenzimidazole ion exchange membrane containing quaternary ammonium side chains is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a method for synthesizing a polybenzimidazole ion exchange membrane containing a quaternary ammonium side chain to solve the existing problems.
[0006] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for synthesizing a polybenzimidazole ion exchange membrane containing a quaternized side chain, comprising the following steps:
[0008] S1. Dissolve 5% to 20% wt polybenzimidazole and 5% to 30% wt polyvinylbenzyl chloride in one or more of dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide, respectively, and stir at 50-70° C. for 4-6 hours until the two are completely dissolved to form a solution;
[0009] S2, mixing polybenzimidazole and polyvinyl benzyl chloride solution in a certain proportion and stirring at 50° C. for 24 hours;
[0010] S3, then use a coating machine to prepare it into a film at a rate of 2mm / S, the drying temperature is 80-120°C, and the finished film specifications have thicknesses of 15, 20, 25 and 30um;
[0011] S4, cutting the membrane into 5 cm squares, soaking it in a quaternary ammonium salt solution such as triethylamine, triethylenediamine or one or more organic solutions of other quinines at a temperature of 50-90°C and a concentration of 0.02-1.0 mol / L for 1-12 hours;
[0012] S5, then rinse with deionized water, and then use 0.1-2.0 mol / L alkali solution for cation replacement for 1-6 hours;
[0013] S6. Finally, the mixture is rinsed with deionized water to obtain a quaternized polybenzimidazole ion exchange membrane having a cross-linked network.
[0014] Furthermore, in step S1, two solutions may be mixed into a solvent to form a blended solution with different mass ratios of 1:2, 1:3 or 1:4 to increase the dissolution rate of the powder.
[0015] The present invention has the following beneficial effects:
[0016] In the present invention, by introducing a side chain monomer containing a quaternary ammonium salt group, the ion exchange sites of the membrane are significantly increased, thereby providing a higher ion exchange capacity.
[0017] In the present invention, the introduction of quaternary ammonium salt groups optimizes the transmission channel of anions, reduces the ion migration resistance, and thus improves the conductivity of the membrane.
[0018] In the present invention, the addition of the toughening agent significantly improves the mechanical properties of the membrane, making it have good durability and flexibility, prolonging its service life, reducing the frequency of maintenance and replacement, and improving economic benefits.
[0019] In the present invention, a non-fluorinated ion exchange membrane material is developed as a substitute for perfluorosulfonic acid membrane, which reduces the cost and potential impact on the environment.
[0020] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0022] Figure 1 The present invention is a flow chart of a method for synthesizing a polybenzimidazole ion exchange membrane containing quaternary ammonium side chains. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In the description of the present invention, it should be understood that the terms "upper", "middle", "outer", "inner" and the like indicating directions or positional relationships are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the components or elements referred to must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as limiting the present invention.
[0025] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "provided with", "connected", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0026] Embodiment 1
[0027] See also Figure 1 As shown, the present invention is a method for synthesizing a polybenzimidazole ion exchange membrane containing a quaternary ammonium side chain, comprising the following steps:
[0028] S1, dissolving 5% to 20% wt polybenzimidazole and 5% to 30% wt polyvinylbenzyl chloride in dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide, respectively, and stirring at 50-70° C. for 4-6 hours until completely dissolved to form a solution;
[0029] S2, mixing polybenzimidazole and polyvinyl benzyl chloride solution in a certain proportion and stirring at 50° C. for 24 hours;
[0030] S3, then use a coating machine to prepare it into a film at a rate of 2mm / S, the drying temperature is 80-120°C, and the finished film specifications have thicknesses of 15, 20, 25 and 30um;
[0031] S4, cutting the membrane into 5 cm squares, soaking in a quaternary ammonium salt solution such as triethylamine, triethylenediamine or other quinine solution of the present embodiment or multiple organic solutions at a temperature of 50-90° C. and a concentration of 0.02-1.0 mol / L for 1-12 hours;
[0032] S5, then rinse with deionized water, and then use 0.1-2.0 mol / L alkali solution for cation replacement for 1-6 hours;
[0033] S6. Finally, the mixture is rinsed with deionized water to obtain a quaternized polybenzimidazole ion exchange membrane having a cross-linked network.
[0034] In step S1, two solutions can be mixed into a solvent to form a blended solution with different mass ratios of 1:2, 1:3 or 1:4 to increase the dissolution rate of the powder.
[0035] Embodiment 2
[0036] This embodiment is a method for synthesizing a polybenzimidazole ion exchange membrane containing quaternized side chains, comprising the following steps:
[0037] S1. Dissolve 5%wt polybenzimidazole and 30%wt polyvinylbenzyl chloride in a mixed solution of dimethylacetamide and N-methylpyrrolidone in a mass ratio of 1:2, respectively, and stir at 50°C for 4 hours until the mixture is completely dissolved to form a solution;
[0038] S2, mixing polybenzimidazole and polyvinyl benzyl chloride solution in a ratio of 1:3 and stirring at 50° C. for 24 hours;
[0039] S3, then use a coating machine to prepare it into a film at a rate of 2mm / S, the drying temperature is 80°C, and the finished film specification thickness is 20um;
[0040] S4, cutting the membrane into 5 cm squares, and soaking it in a triethylamine solution at a temperature of 50°C and a concentration of 0.02 mol / L for 1 hour;
[0041] S5, then rinse with deionized water, and then use 0.1mol / L alkali solution for cation replacement for 1 hour;
[0042] S6. Finally, the mixture is rinsed with deionized water to obtain a quaternized polybenzimidazole ion exchange membrane having a cross-linked network.
[0043] Embodiment 3
[0044] This embodiment is a method for synthesizing a polybenzimidazole ion exchange membrane containing quaternized side chains, comprising the following steps:
[0045] S1. Dissolve 10%wt polybenzimidazole and 25%wt polyvinylbenzyl chloride in a mixed solution of N-methylpyrrolidone and dimethyl sulfoxide in a mass ratio of 1:4, respectively, and stir at 60°C for 5 hours until the mixture is completely dissolved to form a solution;
[0046] S2, mixing polybenzimidazole and polyvinyl benzyl chloride solution in a ratio of 1:2 and stirring at 50° C. for 24 hours;
[0047] S3, then use a coating machine to prepare it into a film at a rate of 2mm / S, the drying temperature is 90°C, and the finished film specification thickness is 20um;
[0048] S4, cutting the membrane into 5 cm squares, and soaking it in a triethylenediamine solution with a temperature of 60°C and a concentration of 0.05 mol / L for 2 hours;
[0049] S5, then rinse with deionized water, and then use 0.2mol / L alkali solution for cation replacement for 1 hour;
[0050] S6. Finally, the mixture is rinsed with deionized water to obtain a quaternized polybenzimidazole ion exchange membrane having a cross-linked network.
[0051] Embodiment 4
[0052] This embodiment is a method for synthesizing a polybenzimidazole ion exchange membrane containing quaternized side chains, comprising the following steps:
[0053] S1. Dissolve 15%wt polybenzimidazole and 20%wt polyvinylbenzyl chloride in pure dimethyl sulfoxide solution respectively, and stir at 70°C for 6 hours until they are completely dissolved to form a solution;
[0054] S2, mixing polybenzimidazole and polyvinyl benzyl chloride solution in a ratio of 1:4 and stirring at 50° C. for 24 hours;
[0055] S3, then use a coating machine to prepare it into a film at a rate of 2mm / S, the drying temperature is 100°C, and the finished film specification thickness is 25um;
[0056] S4, cutting the membrane into 5 cm squares, and soaking it in a triethylamine solution with a temperature of 70°C and a concentration of 0.1 mol / L for 3 hours;
[0057] S5, then rinse with deionized water, and then use 0.5mol / L alkali solution for cation replacement for 3 hours;
[0058] S6. Finally, the mixture is rinsed with deionized water to obtain a quaternized polybenzimidazole ion exchange membrane having a cross-linked network.
[0059] Embodiment 5
[0060] This embodiment is a method for synthesizing a polybenzimidazole ion exchange membrane containing quaternized side chains, comprising the following steps:
[0061] S1. Dissolve 20%wt polybenzimidazole and 15%wt polyvinylbenzyl chloride in a mixed solution of dimethylacetamide and N-methylpyrrolidone in a mass ratio of 1:3, respectively, and stir at 65°C for 5.5 hours until the mixture is completely dissolved to form a solution;
[0062] S2, mixing polybenzimidazole and polyvinyl benzyl chloride solution in a ratio of 1:3 and stirring at 50° C. for 24 hours;
[0063] S3, then use a coating machine to prepare it into a film at a rate of 2mm / S, the drying temperature is 110°C, and the finished film specification thickness is 30um;
[0064] S4, cutting the membrane into 5 cm squares, and soaking it in a triethylenediamine solution with a temperature of 80°C and a concentration of 0.15 mol / L for 4 hours;
[0065] S5, then rinse with deionized water, and then use 1.0 mol / L alkali solution for cation replacement for 4 hours;
[0066] S6. Finally, the mixture is rinsed with deionized water to obtain a quaternized polybenzimidazole ion exchange membrane having a cross-linked network.
[0067] Embodiment 6
[0068] This embodiment is a method for synthesizing a polybenzimidazole ion exchange membrane containing quaternized side chains, comprising the following steps:
[0069] S1, dissolving 8%wt polybenzimidazole and 27%wt polyvinylbenzyl chloride in a mixed solution of N-methylpyrrolidone and dimethyl sulfoxide in a mass ratio of 1:2, respectively, and stirring at 60°C for 4 hours until the mixture is completely dissolved to form a solution;
[0070] S2, mixing polybenzimidazole and polyvinyl benzyl chloride solution in a ratio of 1:2 and stirring at 50° C. for 24 hours;
[0071] S3, then use a coating machine to prepare it into a film at a rate of 2mm / S, the drying temperature is 95°C, and the finished film specification thickness is 20um;
[0072] S4, cutting the membrane into 5 cm squares, and soaking it in a triethylenediamine solution with a temperature of 65°C and a concentration of 0.08 mol / L for 2.5 hours;
[0073] S5, then rinse with deionized water, and then use 0.3 mol / L alkali solution for cation replacement for 2.5 hours;
[0074] S6. Finally, the mixture is rinsed with deionized water to obtain a quaternized polybenzimidazole ion exchange membrane having a cross-linked network.
[0075] Table 1 is the experimental test results of the above-mentioned preparation of polybenzimidazole ion exchange membrane samples
[0076]
[0077] Experimental results show that the present invention has developed a non-fluorinated membrane material based on polybenzimidazole, which has excellent thermomechanical properties and chemical stability, can effectively replace traditional perfluorosulfonic acid membranes, reduce costs and reduce environmental impact.
[0078] In the present invention, polybenzimidazole and polyvinylbenzyl chloride are blended and quaternary ammonium salt functionalized side chains are introduced to create a novel cross-linked interpenetrating network structure, which significantly improves the ion exchange capacity and conductivity of the membrane while maintaining low vanadium ion permeability.
[0079] The present invention optimizes the mechanical properties, chemical stability and electrochemical properties of the membrane by systematically adjusting the ratio of polybenzimidazole and polyvinylbenzyl chloride in the blended membrane and the type and amount of quaternary ammonium salt, thereby improving the environmental adaptability and application potential of the membrane while improving the battery efficiency and life.
[0080] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0081] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for synthesizing a polybenzimidazole ion exchange membrane containing a quaternized side chain, characterized in that: The following steps are involved: S1. Dissolve 5% to 20% wt polybenzimidazole and 5% to 30% wt polyvinylbenzyl chloride in one or more of dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide, respectively, and stir at 50-70° C. for 4-6 hours until the two are completely dissolved to form a solution; S2, mixing polybenzimidazole and polyvinyl benzyl chloride solution in a certain proportion and stirring at 50° C. for 24 hours; S3, then use a coating machine to prepare it into a film at a rate of 2mm / S, the drying temperature is 80-120°C, and the finished film specifications have thicknesses of 15, 20, 25 and 30um; S4, cutting the membrane into 5 cm squares, soaking it in a quaternary ammonium salt solution such as triethylamine, triethylenediamine or one or more organic solutions of other quinines at a temperature of 50-90°C and a concentration of 0.02-1.0 mol / L for 1-12 hours; S5, then rinse with deionized water, and then use 0.1-2.0 mol / L alkali solution for cation replacement for 1-6 hours; S6. Finally, the mixture is rinsed with deionized water to obtain a quaternized polybenzimidazole ion exchange membrane having a cross-linked network.
2. The method for synthesizing a polybenzimidazole ion exchange membrane containing quaternized side chains according to claim 1, characterized in that: In the step S1, two solutions may be mixed into a solvent to form a blended solution with different mass ratios of 1:2, 1:3 or 1:4 to increase the dissolution rate of the powder.